Analysis of Extracurricular Participants' Sepak Sila Skills - Hasanuddin, M. Imran; Hasyim, Hasyim (Universitas PGRI Palembang, 2024)
This research is a Descriptive Research that aims to determine the Analysis of Sepak Takraw Skills of Extracurricular Participants of SMK Negeri 2 Makassar. Data collection uses documentation from test results that include data on Basic Sepak Takraw Technique Skills. The variables in this study are Sepak Takraw Skills in Sepak Takraw Games in Extracurricular Participants of SMK Negeri 2 Makassar. The population taken from 20 students in this study were Extracurricular Participants of SMK Negeri 2 Makassar while the sample determination used the Total Sampling method of Extracurricular Participants of SMK Negeri 2 Makassar as many as 20 students. The data from the research obtained the percentage of Sepak Takraw Skills data from 20 students or (100%), the Very Good category was 1 student or (5%), the Good category was 6 students or (30%), the Moderate category was 10 students or (50%), the less category was 3 students or (15%), and the Less Category was 0 students or (0.0%). Thus, it can be concluded that the percentage of the final data results of Sepak Takraw Skills in the Sepak Takraw Game of Extracurricular Participants at SMK Negeri 2 Makassar is in the Medium category.